Tongdosa Museum 04 - Bernard Gagnon (Wikimedia Commons, 2022)
Notice iconographique issue de Wikimedia Commons. Titre: Tongdosa Museum 04. Painting in Tongdosa Museum near Yangsan, South Korea
Licence Creative Commons Zero, Public Domain Dedication via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons